Germline natural killer cell receptors modulating the T cell response - Mora-Bitria, Laura; Asquith, Becca (Frontiers in Immunology, 2024)
In addition to their central role during innate responses, NK cells regulate adaptive immunity through various mechanisms. A wide array of innate receptors has been involved in the NK cell regulatory function. However, the clinical implications of these regulatory pathways are poorly understood. Here, we review the experimental evidence on the effects of NK cells on T cells and their positive and negative consequences for disease outcome during T cell responses in humans.